2017
DOI: 10.3390/app7040323
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Design of Hybrid Interstory-Interbuilding Multi-Actuation Schemes for Vibration Control of Adjacent Buildings under Seismic Excitations

Abstract: Abstract:The design of vibration control systems for the seismic protection of closely adjacent buildings is a complex and challenging problem. In this paper, we consider distributed multi-actuation schemes that combine interbuilding linking elements and interstory actuation devices. Using an advanced static output-feedback H ∞ approach, active and passive vibration control systems are designed for a multi-story two-building structure equipped with a selected set of linked and unlinked actuation schemes. To va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…In general, passive damping devices have the advantages of simple structure, easy maintenance, and high reliability, and have been widely implemented in mechanical, civil, and aerospace structures [43,44]. Commonly used passive vibration dampers include TMDs (tuned mass damper) [45,46], viscoelastic dampers, impact dampers [47,48], particle dampers [49,50], oil dampers, friction dampers [51,52], shape memory alloy (SMA) dampers [53][54][55], eddy current dampers [56][57][58], among others [59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…In general, passive damping devices have the advantages of simple structure, easy maintenance, and high reliability, and have been widely implemented in mechanical, civil, and aerospace structures [43,44]. Commonly used passive vibration dampers include TMDs (tuned mass damper) [45,46], viscoelastic dampers, impact dampers [47,48], particle dampers [49,50], oil dampers, friction dampers [51,52], shape memory alloy (SMA) dampers [53][54][55], eddy current dampers [56][57][58], among others [59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…For the particular case of m = 2 adjacent buildings, the number of references is remarkably smaller but yet significant. Works in this line include different kinds of interbuilding damping devices [17][18][19] and actuation schemes [20][21][22]. In contrast, to our best knowledge, the more general case of DDS design for MBSs with m ≥ 3 adjacent buildings remains practically unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…It should be observed that the DDS implementation can be carried out without internal modifications of nonactuated buildings, which can be an important factor in retrofitting. The relevance of linked configurations lies in the fact that they can help to mitigate the vibrational response of nonactuated buildings and can also provide an effective protection against interbuilding impacts (pounding) [22,23]. To incorporate those aspects in the DDS design and reducing the number of optimization variables, we introduce the schemes of allowed damper positions, which specify the interstory and interbuilding locations where the dampers can be implemented.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of civil engineering vibration control, passive control [19][20][21][22], semi-active control [23][24][25], active control [26][27][28], and hybrid control [29][30][31][32] have been extensively studied and demonstrated. In particular, passive control is the most widely used type of control system due to its simple structure, easy maintenance and high reliability [33][34][35].…”
Section: Introductionmentioning
confidence: 99%